Tourist-Cultural Routes and Itineraries in the Official Tourism Portals of the Spanish Autonomous Communities. - Calderón-Puerta, Diego Manuel; Arcila-Garrido, Manuel Luis; López-Sánchez, José Antonio (Revista de Estudios Andaluces, 2018)
In the last decades, cultural tourism has become an alternative to other tourist typologies, since a more complementary offer is necessary. This expansion of culture as a tourism product has led to the proliferation of routes and tourist-cultural itineraries, promoted by regional, national and international organizations. These tourist realities have generated a multitude of definitions by organisms and authors, giving rise to a debate on two concepts that although they share similarities can be considered different. In the diffusion, creation and recognition of routes and itineraries, the different Spanish autonomous governments play a fundamental role. In this sense, through the creation of official websites, the Autonomous Communities try to publicize their culture and their tourism products. On the one hand, the objective of this work is to analyze the concepts of cultural tourism route and itinerary, on the other hand the dissemination of tourist routes and the treatment of itineraries by the Autonomous Communities in their official portals will be studied.